KONTRIBUSI KOORDINASI MATA-KAKI DAN KEKUATAN OTOT TUNGKAI TERHADAP KETERAMPIAN SHORT PASS PADA PESERTA EKSTRAKURIKULER FUTSAL DI MAN 1 PEKANBARU - Beny Guswira Kurniawan; Saripin Saripin; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the contribution of food-eyes coordination and strenght of leg muscle toward the short pass skills at students following extracurricular futsal activities in MAN 1 Pekanbaru. Population of this research is students following extracurricular futsal activities in MAN 1 Pekanbaru totaling 20 students. The sampling technique in this research is all of population at extracurricular futsal activities totaling 20 students. This research use the soccer wall voley test, leg dynamo meter and passing stopping test. Data analysis techniques in this research use product moment correlation and multiple correlation. The results of this research is there are the contribution of food-eyes coordination toward the sort pass skills, with correlation is Rx1y = 0,462 and contribution given is 21,32% with the medium correlation. There is contribution of strenght of leg muscle toward the short pass skills, with correlation is Rx2y = 0,459 and contribution given is 21,03% with the medium correlation. There is contribution of food-eyes coordination and strenght of leg muscle toward the short pass skills, with correlation is Rx1x2y = 0,601 and contribution given is 36,17% with the strong correlation.Keywords: Foot-eyes coordination, strenght of leg muscle, short pass skills, futsal.